Reviews of fungi and mycotoxins in Chinese dark tea - Xu, Wei; Zhao, Yi-qiao; Jia, Wen-bao; Liao, Si-yu; Bouphun, Tunyaluk; Zou, Yao (Frontiers in Microbiology, 2023)
Dark tea is a unique post-fermented tea with microorganisms involved in the transformation of substances, which is widely appreciated by consumers. The fermentation is the main process to form the unique flavor and health benefits of dark tea. Numerous studies have indicated that the microorganisms play a significant part in the fermentation process of dark tea. Dark tea has the quality of "The unique flavor grows over time", and the value of aged dark tea increases with the year of storage, but unscientific storage of dark tea might cause infestation of harmful microorganisms, thereby resulting in the remaining of fungi toxins. Mycotoxins are a kind of secondary metabolites with biologically toxic produced by fungi, which are regarded as the main contributor to the quality of dark tea, and its potential mycotoxin risk has attracted people's attention. This study reviews common and potential mycotoxins in dark tea and discusses the possible types of masked mycotoxins in dark tea. Summary of the potential risks of mycotoxins and masked mycotoxins in dark tea is presented, intend to provide a reference for the prevention and risk assessment of harmful fungi in dark tea.